ANALYSIS OF THE ROLE OF CODIFICATION TO SUPPORT THE PLANNED MAINTENANCE SYSTEM (PMS) THE MAIN TOOL OF THE NAVY WEAPONS SYSTEM - Hariyanto Hariyanto; Suparno Suparno; Joko Purnomo (STTAL POSTGRADUATE - INTERNATIONAL CONFERENCE, 2021)
ABSTRACT The material codification system is deliberately designed to realize effectiveness and efficiency in providing defense logistics support and facilitate better management of equipment and supplies materiel data. The main tool of the navy weapons system consisting of ships, aircraft, marines and bases including personnel who manned. The preparation of adequate logistical support it, will have an impact on the readiness of the main tool of the navy weapons system in carrying out its duties and functions. This research aims to improve the implementation of codification embodied in the completeness of the Material Basic Book (MBB) in The main tool of the navy weapons system so that it will support the preparedness of the Navy in carrying out operations and exercises. To examine the above problems, identification is needed to answer the current problem by using swot analysis method approach. In this approach, the right decision is also done in making decisions using SWOT matrix calculations that can produce the best strategy formulation by providing weight and rating values from internal and external factors against four quadrants so that it is known that the result is in quadrant III which supports turn around strategy with a difference between strength and weakness of 1 while the odds and threats are 2.62. Keywords: Codification, Supply, and SWOT